Induction, immobilization, modification and natural inhibitors of α-glucosidase from Penicillum chrysogenum - Hamed M. El-Shora; Saida M. Messgo; Mohsen E. Ibrahim; Mohamed W alfakharany (International Journal of Phytomedicine, 2018)
α-glucosidase (EC: 3.2.1.20) was isolated from Penicillum chrysogenum. The enzyme was enhanced by plant growth regulators such as gibberellic acid (GA3), benzylaminopurine (BAP) and kinetin. Dansyl chloride inhibited the enzyme at 1, 2, 3, 4 and 5 mM with T0.5 67, 52.2, 34.4 and 23.3 min, respectively. The substrate offered partial protection for the enzyme against dansyl chloride inhibition. The enzyme was activated by Ca2+ and Mg2+. However, Pb2+, Cd2+, Zn2+, Ni2+ and Hg2+ inhibited α-glucosidase activity. The enzyme was immobilized on Ca alginate and the optimal concentration for 3% w/v. The optimal concentration of CaCl2 was recorded at 3 mM. The optimal CaCl2 concentration and the optimum time for immobilization was 3mM and 4hr. The enzyme was inhibited by aqueous extracts of Datura stramonium, Trigonella foenum-graecum, Hyoscymus muticus and Cynodon dactylon. The IC50 values for the four extracts were 59.1, 73.6, 68.5 and 77.1 µg ml-1, respectively.